Study on Tire-attached Energy Harvester for Low-speed Actual Vehicle Driving. (November 2015) - Zhang, Y; Zheng, R; Kaizuka, T; Su, D; Nakano, K
Abstract: This study reports a tire-attached energy harvester, in which a cantilever beam pasted piezoelectric film and magnets with the same polarity are fabricated as a bistable vibrating system, for low-speed actual-vehicle driving. As the wheel rotates, the energy harvester is subjected to the noise produced from the interaction between the paved road and the rotating tire, and tangentially gravitational force as a periodic input can be applied to achieve the occurrence of stochastic resonance. Stochastic resonance can significantly stimulate the response of the bistable vibrating system, and therefore enhance the energy harvesting efficiency.